Effects of CuO doping on structure, microstructure and dielectric properties of BaTiO3–PbTiO3 solid solution - Garbarz-Glos, Barbara; Bąk, Wojciech; Kalvane, Anna; Antonova, Maija; Klimkowski, Grzegorz (Taylor and Francis Ltd., 2019)
Ba0.7Pb0.3TiO3 and Ba0.7Pb0.3TiO3+yCuO (y = 0.1 wt%, 0.5 wt%, 1 wt% and 3 wt%) samples were prepared by a solid state reaction method. High purity raw materials were used. Structural properties of the sintered pellets were studied by X-ray diffractometer X’Pert PRO (PANalytical). A single phase of perovskite structure with tetragonal phase was identified at room temperature. The surface morphology of the obtained specimens was characterized by the scanning electron microscopy (Hitachi S4700). The investigations has shown that the synthesized ceramic materials are characterized by the high density, homogeneity of microstructure and low porosity. Dielectric spectroscopy was used to study the electrical properties of the solid solution on the basis of BaTiO3 doped CuO.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Solid solution; barium titanate; microstructure; dielectric properties